Physiological characterization and bioactive compounds of promising accessions of cowpea (Vigna unguiculata L. Walp) in the Peruvian Amazon - Murga-Orrillo, Hipolito; Chuquímez Gonzales, Jhon K.; Arévalo López, Luis A. (Frontiers in Agronomy, 2024)
Cowpea production in the Peruvian Amazon is increasing due to its ability to adapt to diverse environments, its contribution to soil conservation, and its versatility of uses. This crop is particularly valuable in human nutrition due to its high nutritional quality and nutraceutical properties of its bioactive compounds. The aim of the study was to evaluate the physiology of cowpea plants in accessions PER1005854, PER1005851, and PER12645, under the influence of rice husk mulch, screw tree litter, and oil palm fiber, as well as to determine the bioactive compounds present in the grains. This study aims to promote sustainable cowpea production, expose the nutritional aspects of the grains, and foster their consumption both locally and nationally. The experiment was conducted from November 2022 to March 2023, in Yurimaguas, Loreto, Peru. The application of organic mulches demonstrates a significantly positive impact on the growth of cowpea accessions during their vegetative phase. This effect is possibly attributed to increased water availability, as the mulch reduces soil evaporation. In particular, cowpea accessions PER12645 and PER1005851 exhibit desirable physiological characteristics for grain production, with short cycles of 71 days and higher yields of 1141 and 1125 kg/ha respectively. In contrast, accession PER1005854 is distinguished by its higher biomass production, reaching a value of 14497 kg/ha, a relevant trait for foliage production and its contribution to soil conservation. The bioactive compounds, such as proteins, lipids, and carbohydrates, present in the accessions PER1005854, PER1005851, and PER12645, are similar to those found in other legumes. However, the antioxidant activity of dark tegument cowpeas proved to be superior, particularly highlighted in accession PER12645 (black tegument) with 26.3 μmolTG/g, and in accession PER1005854 (dark red tegument) with 19.5 μmolTG/g. This characteristic is particularly important for consumption, as it is related to the ability to combat oxidative stress in the human body.